2018
DOI: 10.1159/000495804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mode of Delivery on Early Oral Colonization and Childhood Dental Caries: A Systematic Review

Abstract: This review investigated whether mode of delivery influences the colonization of infant’s oral cavity and the risk of early childhood caries (ECC). The search strategy included systematic searching of electronic databases (Web of Science and PubMed) for articles published (1995–2015) and hand searching of references lists. Outcomes of interest were the presence of oral caries-related microorganisms, oral species considered protective against caries, and dental caries. Other outcomes included severity of dental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…In this study, we found no firm evidence of an elevated prevalence of early childhood caries levels in C-section children. Nevertheless, in contrast to the previous systematic review (Antão et al 2019 ), we noticed a weak but statistically significant tendency towards a higher caries prevalence in the C-section group. The certainty of this finding was, however, low due to inconsistencies and a high risk of bias in the majority of the included publications.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, we found no firm evidence of an elevated prevalence of early childhood caries levels in C-section children. Nevertheless, in contrast to the previous systematic review (Antão et al 2019 ), we noticed a weak but statistically significant tendency towards a higher caries prevalence in the C-section group. The certainty of this finding was, however, low due to inconsistencies and a high risk of bias in the majority of the included publications.…”
Section: Discussioncontrasting
confidence: 99%
“…In this context, the mode of delivery is of particular interest, since the frequency of caesarean section (C-section) on maternal request has increased unprecedented over the recent decades (Begum et al 2020 ) and it is important to have solid information if this may affect the future oral health of the child. To our knowledge, the association between the mode of delivery and ECC has previously been addressed in one systematic review (Antão et al 2019 ). Based on four studies, the authors found no consistent relationship between the birth mode and the caries risk.…”
Section: Introductionmentioning
confidence: 99%
“…26 General opinion was the mode of delivery may lead to differences in the microbial acquisition pattern in the oral cavity but, other factors could modify its effect. 27,28 Therefore, this result should be supported by future microbiological studies about BTS and mode of delivery.…”
Section: Discussionmentioning
confidence: 63%